Molecular Typing of Ukrainian Bacillus anthracis Strains by Combining Whole-Genome Sequencing Techniques - Hanka Brangsch; Anatolii Golovko; Nataliia Pinchuk; Oleg Deriabin; Tetiana Kyselova; Jörg Linde; Falk Melzer; Mandy Carolina Elschner (Microorganisms, 2022)
Anthrax is a recurrent zoonosis in the Ukraine with outbreaks occurring repeatedly in certain areas. For determining whether several Bacillus anthracis genotypes are circulating in this region, four strains from various sources isolated from different regions of the Ukraine were investigated. By combining long- and short-read next-generation sequencing techniques, highly accurate genomes were reconstructed, enabling detailed in silico genotyping. Thus, the strains could be assigned to the Tsiankovskii subgroup of the “TransEurAsia” clade, which is commonly found in this region. Their high genetic similarity suggests that the four strains are members of the endemic population whose progenitor was once introduced in the Ukraine and bordering regions. This study provides information on B. anthracis strains from a region where there is little knowledge of the local population, thereby adding to the picture of global B. anthracis genotype distribution. We also emphasize the importance of surveillance and prevention methods regarding anthrax outbreaks, as other studies predicted a higher number of cases in the future due to global warming.